Modernization and Cultural Shift in Indigenous Communities: Evidence from the Pado’e under Mining Expansion - Lebba Lebba; Muhammad Ali; Abbas Langaji; Munir Yusuf; M. Syafril Marib Setiawan Lebba (KARSA Journal of Social and Islamic Culture, 2026)
This study examines how mining-led modernization has reconfigured the cultural and socio-economic life of the Pado’e indigenous community in East Luwu and evaluates the extent to which PT Vale’s corporate social responsibility (CSR) programs respond to the resulting problems. The study uses a qualitative case-study design with an ethnographic orientation, drawing on fieldwork conducted from June 2021 to January 2022 through semi-structured interviews, direct observation, and documentary analysis. The analysis identifies four interrelated shifts: livelihoods have moved from predominantly subsistence activities toward commercial agriculture, wage labor, entrepreneurship, and greater market dependence; formal education has become a central household aspiration; family authority, gendered mobility, domestic roles, and spouse selection have become more negotiable; and mutual cooperation remains morally important but is less dominant in organizing everyday life. PT Vale’s education, health, agriculture, enterprise, socio-cultural, sports, and infrastructure programs have expanded access to services. However, corporate aggregate data do not show how benefits are distributed among Pado’e households or whether supported livelihoods remain viable without company assistance. The findings, therefore, interpret modernization as a selective reconfiguration of cultural institutions rather than a complete disappearance of tradition, while treating CSR as a partial response that has not resolved historical land grievances, unequal participation, or dependence on the mining economy.